4 Boys, bulk, and body ideals: sex differences in weight gain attempts among adolescents in the united states. (18th November 2019) - Nagata, JM; Bibbins-Domingo, K; Garber, AK; Griffiths, S; Vittinghoff, E; Murray, SB
Abstract : Aim: Research on attempts to gain weight among adolescent males is limited and has not yet been examined using nationally representative samples in the United States. The objective of this study was to estimate the prevalence of weight gain attempts in adolescent boys using a nationally representative sample and to examine differences in weight gain attempts by weight classification, weight self-perception, age, race/ethnicity, and sexual identification. Methods: Participants were 15, 624 high school students from the nationally representative 2015 Youth Risk Behavior Survey. Results: Overall, 29.6% of adolescent boys reported attempts to gain weight, including 39.6% of boys who were normal weight, 12.8% who were overweight, and 10.6% who were obese by body mass index (BMI). In contrast, only 6.5% of adolescent girls reported attempts to gain weight. Although only 3.3% of adolescent males are underweight by BMI, 19.3% perceive themselves to be underweight. Further, over half of adolescent males who are overweight by BMI perceive themselves to be about the right weight. African American (Odds ratio [OR] 1.89; 95% confidence interval [CI] 1.50-2.38) and mixed race (OR 1.62; 95% CI 1.16-2.26) adolescent males had greater odds of weight gain attempts than White adolescent males. Adolescent males identifying as bisexual had lower odds (OR 0.47; 95% CI 0.25 – 0.88) of weight gain attempts than adolescent males identifying as heterosexual. Conclusions: Weight gain attempts are common among adolescent boys including those who are considered normal weight, overweight, or obese by BMI; African American or mixed race; and those self-identifying as heterosexual. Consideration of the unique nature of male body image, particularly adolescent boys' perceptions of their own weight and weight-gain attempts, should be incorporated into primary care screening for adolescent boys.